End user security awareness - Lowrie, Daniel; Pezet, Don (Packt Publishing, 2024)
The course begins with a critical look at password security, emphasizing the importance of robust credentials in protecting personal and professional data. Then, it moves on to social engineering, showing you how hackers trick people into giving away their information. You'll learn the importance of being careful about who you trust online. Next, the course covers how to protect your computers and devices from being physically broken into. It also talks about the right way to get rid of old data so that nobody else can find it. This part is all about keeping your stuff safe in the real world. The course also looks at safe and unsafe networks. You'll learn how to check if a network is secure and what to do when using a risky one. Finally, the course dives into malicious software or malware. You'll find out what it is, how to spot it, and how to keep it from messing up your devices. By the end, you'll know how to protect yourself from a lot of the dangers on the internet, turning you from a beginner to someone who's smart about online security. What you will learn Secure passwords with best practices Conduct safe data disposal protocols Navigate networks with safety measures Identify various forms of malicious software Apply defenses against software threats Adopt proactive cyber hygiene habits Audience This course is ideal for individuals looking to bolster their digital security acumen. Tailored for users who wish to protect their online presence against evolving cybersecurity threats. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Daniel Lowrie: Daniel Lowrie's IT career began with workstation support and Y2K compliance updates for a teaching hospital in North-Central Florida. His journey led him to become an in-classroom trainer and Mentored Learning Instructor, specializing in courses covering Microsoft Windows Desktops and Servers, Active Directory, Networking, CCNA, and Linux. He then transitioned to becoming a Systems and Network administrator for a large insurance company before joining ACI Learning as an Edutainer. Certifications: CompTIA A+, Network+, Linux+, CySA+, and PenTest+; CEH; MCSA; CFR; eJPT Don Pezet: Don Pezet, with over 25 years in IT, brings rich experience from his time as a field engineer in finance and insurance, supporting networks globally. A Linux enthusiast, he's skilled in Red Hat and Ubuntu, and has a long-standing connection with macOS and Apple products since the mid-90s. For the last 15 years, Don has dedicated himself to IT education, co-founding ITProTV in 2012 to provide top-tier IT training. As ACI Learning's CPO, he continues to deliver innovative training to IT professionals. His credentials include Microsoft MCSE, Amazon ACSA, Cisco CCNP, LPI LPIC-2, PMI PMP, and several CompTIA certifications like A+, Network+, Security+, and Linux+.
Online resource; title from title details screen (O'Reilly, viewed March 4, 2024)
Keywords: Computer networks -- Security measures; Computer security; Réseaux d'ordinateurs; Sécurité; Mesures; Sécurité informatique; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet